Influência da dexmedetomidina associada à atropina sobre os índices globais de perfusão em cães anestesiados com isoflurano submetidos á hemorragia seguida por reposição volêmica com sangue autólogo - Cândido, Thaísa David [UNESP] (2014)
Early recognition and treatment of acute intraoperative hemorrhage is seminal for preventing the morbidity and mortality associated with circulating volume losses. On the other hand, dexmedetomidine is an adjuvant anesthetic drug that might aggravate global tissue hypoperfusion induced by acute hemorrage because of its vasopressor effects. This study aimed to evaluate the effects of a constant rate infusion of dexmedetomidine combined with atropine on global perfusion indexes and on other hemodynamic parameters in isoflurane anesthestized dogs that underwent a volume-guided hemorrhage model followed by volume replacement with autologous blood. Eight healthy dogs (19-30 kg) were anesthetized in two occasions with equipotent concentrations (1.3 minimum alveolar concentration) of isoflurne alone (treatment ISO) or isoflurane combined with dexmedetomidine (1.6 μg/kg bolus, followed by 2 μg/kg/h) (treatment ISO-DEX) in a randomized crossover design, allowing 2-week intervals between treatments. Atropine (0,03 mg/kg, IM and 0.01 mg/kg IV) was administered 30 minutes prior to hemorrhage in the dexmedetomidne treatment. Anesthesia was maintained in both treatments under neuromuscular blockade induced by atracurium and volume controlled ventilation (expired tidal volume: 12 mL/kg, positive end-expiratory pressure: 7 cm H2O, respiratory rate: 16-20 mov/min). After recording pre-hemorrhage data (baseline), stepwise withdrawal of 10, 20, and 30% of the estimated blood volume (80 mL/kg) was followed by volume replacement with autologous blood in the same proportion. When compared with baseline values, hemorrhage significantly (P < 0,05) reduced oxygen delivery índex (IDO2) and mixed-venous saturation (SvO2) in both treatments. Although the oxygen extraction ratio (O2ER) was increased (P < 0.05) from baseline during hemorrhage, the anaerobic threshold (point where the oxygen comsumption (IVO2) becomes dependent on the IDO2] was not reached in both ...